Effects of foot strike techniques on running biomechanics: A systematic review and meta-analysis - Xu, Y.; Yuan, P.; Wang, R.; Wang, D.; Liu, J.; Zhou, H. (Sports Health: A Multidisciplinary Approach, 2021)
Content: Distance running is one of the most popular physical activities, and running-related injuries (RRIs) are also common. Foot strike patterns have been suggested to affect biomechanical variables related to RRI risks. Objective: To determine the effects of foot strike techniques on running biomechanics. Data Sources: The databases of Web of Science, PubMed, EMBASE, and EBSCO were searched from database inception through November 2018. Study Selection: The initial electronic search found 723 studies. Of these, 26 studies with a total of 472 participants were eligible for inclusion in this meta-analysis. Study Design: Systematic review and meta-analysis. Level of Evidence: Level 4. Data Extraction: Means, standard deviations, and sample sizes were extracted from the eligible studies, and the standard mean differences (SMDs) were obtained for biomechanical variables between forefoot strike (FFS) and rearfoot strike (RFS) groups using a random-effects model. Results: FFS showed significantly smaller magnitude (SMD, -1.84; 95% CI, -2.29 to -1.38; P < 0.001) and loading rate (mean: SMD, -2.1; 95% CI, -3.18 to -1.01; P < 0.001; peak: SMD, -1.77; 95% CI, -2.21 to -1.33; P < 0.001) of impact force, ankle stiffness (SMD, -1.69; 95% CI, -2.46 to -0.92; P < 0.001), knee extension moment (SMD, -0.64; 95% CI, -0.98 to -0.3; P < 0.001), knee eccentric power (SMD, -2.03; 95% CI, -2.51 to -1.54; P < 0.001), knee negative work (SMD, -1.56; 95% CI, -2.11 to -1.00; P < 0.001), and patellofemoral joint stress (peak: SMD, -0.71; 95% CI, -1.28 to -0.14; P = 0.01; integral: SMD, -0.63; 95% CI, -1.11 to -0.15; P = 0.01) compared with RFS. However, FFS significantly increased ankle plantarflexion moment (SMD, 1.31; 95% CI, 0.66 to 1.96; P < 0.001), eccentric power (SMD, 1.63; 95% CI, 1.18 to 2.08;P < 0.001), negative work (SMD, 2.60; 95% CI, 1.02 to 4.18; P = 0.001), and axial contact force (SMD, 1.26; 95% CI, 0.93 to 1.6; P < 0.001) compared with RFS. Conclusion: Running with RFS imposed higher biomechanical loads on overall ground impact and knee and patellofemoral joints, whereas FFS imposed higher biomechanical loads on the ankle joint and Achilles tendon. The modification of strike techniques may affect the specific biomechanical loads experienced on relevant structures or tissues during running.